Survey of the Importance of Using Basic Biomedical Science Lecture Guidebooks Containing Personality Types for Health Faculty Students - Makiyah, Arfatul; Ramadani, Anggun Fajar (Journal Of Biology Education Research (JBER), 2024)
In higher education, especially in the health sector, a deep understanding of the course material is the key to academic success. In improving the quality of student learning, the use of teaching materials is essential to achieve competency targets. However, each student has a different personality so that their learning style type is different. Based on this, it is necessary to develop more adaptive learning resources that not only include scientific materials, but also pay attention to the different personality types of students. This study aims to explore the importance of using basic biomedical science lecture guidebooks that are tailored to the personality types of students at the Faculty of Health. This research method uses a descriptive survey approach with a purposive sampling technique. A survey was conducted on a number of students to assess the effectiveness and needs of guidebooks designed based on personality types. The survey results showed that most students felt helped by the existence of guides that were in accordance with their learning characteristics, which ultimately improved understanding and academic achievement. It can be concluded that personalized teaching materials according to student personality are useful and needed in the learning process.